Master’s Students’ Perceptions and Expectations of Good Tutors and Advisors in Distance Education - Kara, Mehmet; Can, Gülfidan (International Review of Research in Open and Distributed Learning, 2019)
The purpose of this study was to explore non-thesis Master’s students’ perceptions and expectations of good tutors and advisors in distance education programmes. It also examined whether these perceptions and expectations are related to student characteristics including age, gender, university, programme, semester, and previous online learning experience. The current study was conducted within the framework of Transactional Distance Theory. Using a mixed methods approach, a questionnaire was administered to 143 students in four programmes in two universities in Turkey and interviews were conducted with 11 of these students. Results showed that good tutors and advisors in distance education provide a stimulating student-centred learning environment, have a caring and individualised interaction and communication with students, and have subject expertise and basic technology skills. The results of this study will improve distance education tutors and advisors’ practices in supporting graduate students’ education and research.